2003
DOI: 10.1046/j.1529-8019.2003.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of chronic actinic dermatitis

Abstract: Chronic actinic dermatitis, synonymous with the photosensitivity dermatitis and actinic reticuloid syndrome, presents as a dermatitis and/or a pseudolymphomatous eruption. Abnormal photosensitivity to ultraviolet (UV) and often visible radiation is a feature. Many patients also have multiple contact allergens. Histopathologic features vary, with a spectrum from mild dermatitis to pseudolymphomatous (reticuloid) features. The essential tests to make the diagnosis and to guide advice on avoidance of the responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 51 publications
4
60
0
1
Order By: Relevance
“…128,[145][146][147][148][149][150] Some consider it the first choice for long-term immunosuppression of this condition. 151 Azathioprine has also been reported to be helpful in severe polymorphous light eruption. 152 Other uses Azathioprine has been reported to be successful not only in immunobullous, photodermatotic, and eczematous diseases but also in a number of other severe or recalcitrant conditions.…”
Section: Photodermatosesmentioning
confidence: 99%
“…128,[145][146][147][148][149][150] Some consider it the first choice for long-term immunosuppression of this condition. 151 Azathioprine has also been reported to be helpful in severe polymorphous light eruption. 152 Other uses Azathioprine has been reported to be successful not only in immunobullous, photodermatotic, and eczematous diseases but also in a number of other severe or recalcitrant conditions.…”
Section: Photodermatosesmentioning
confidence: 99%
“…22,32 Dawe et al 7 found that it is estimated that the probability of resolution is 10% over 5 years, 20% over 10 years, and 50% over 15 years. 22,32 Dawe et al 7 found that it is estimated that the probability of resolution is 10% over 5 years, 20% over 10 years, and 50% over 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients also have multiple contact allergens (Dawe, Crombie, & Ferguson, 2000). Current management for CAD includes broad-spectrum sunscreens, physical protection from sunlight, allergen avoidance, topical corticosteroids and tacrolimus, systemic corticosteroids and immunosuppressive agents such as azathioprine, cyclosporine, and mycophenolate mofetil, and photo(chemo)therapy (Dawe & Ferguson, 2003;Forsyth & Millard, 2010;Ma & Lu, 2010). Current management for CAD includes broad-spectrum sunscreens, physical protection from sunlight, allergen avoidance, topical corticosteroids and tacrolimus, systemic corticosteroids and immunosuppressive agents such as azathioprine, cyclosporine, and mycophenolate mofetil, and photo(chemo)therapy (Dawe & Ferguson, 2003;Forsyth & Millard, 2010;Ma & Lu, 2010).…”
Section: Introductionmentioning
confidence: 99%